Kajian Psikolingusitik: Analisis Gangguan Berbahasa Tokoh Kakak dalam Film My Stupid Brother - Pitriyasari Pitriyasari; Hanifa Yuti Islamiyah; Afiyah Masruri; Fatmawati Fatmawati (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
In the study of psycholinguistics, there are several discussions that are studied, one of which is language disorders. Language disorders are disorders that occur in the brain system and speech organs that inhibit the language system found in humans. This language disorder causes obstruction in the process of interaction and communication between humans. The method used in this study uses descriptive qualitative methods. Furthermore, in this study there is also a discussion focus on autism figures in the film My Stupid Brother. The word autism comes from autos which means self and ism which means a stream. Autism is a flow in which a person is only interested in his own world. Autism is a form of deficiency that occurs while in the womb resulting in weaknesses in the process of interaction, communication, behavior and so on.